2003
DOI: 10.1086/345441
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Risk Profiles for and Mortality Associated with Invasive Aspergillosis among Liver Transplant Recipients

Abstract: To discern whether the characteristics and outcome of invasive aspergillosis in liver transplant recipients have evolved during the past decade, 26 patients who underwent transplantation during 1990-1995 (known as "the earlier cohort") were compared with 20 patients who underwent transplantation during 1998-2001 (known as "the later cohort"). Twenty-three percent of the Aspergillus infections in the earlier cohort occurred у90 days after transplantation, compared with 55% of such infections in the later cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
200
2
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(215 citation statements)
references
References 17 publications
(40 reference statements)
9
200
2
4
Order By: Relevance
“…1 Renal replacement therapies, including hemodialysis, increase risk by about 15-to 25-fold. 3,4 In our case, the patient had acute renal failure within the first week posttransplant and underwent hemodialysis, which increased the risk for invasive aspergillosis, in accordance with risk factors shown in the literature.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…1 Renal replacement therapies, including hemodialysis, increase risk by about 15-to 25-fold. 3,4 In our case, the patient had acute renal failure within the first week posttransplant and underwent hemodialysis, which increased the risk for invasive aspergillosis, in accordance with risk factors shown in the literature.…”
Section: Discussionsupporting
confidence: 86%
“…5,6 Recent cohort studies have shown that there is a tendency for invasive aspergillosis to develop at late onset, with median time found to be 60 days posttransplant. 3 The shift of infection incidence in later stages might be due to improved surgical techniques, better follow-up, and decreased incidence of risk factors, such as cytomegalovirus infection during the early posttransplant period. Our patient had pulmonary symptoms at day 26 posttransplant, and a positive galactomannan at day 32 when the antifungal treatment was started.…”
Section: Discussionmentioning
confidence: 99%
“…Systemische Pilzinfektionen gehören zu den klassischen opportunistischen Erkrankungen bei transplantierten Personen, mit hohen Morbiditäts-und Letalitätsraten [23,24,26]. Die Inzidenz von Pilzinfektionen variiert je nach Quelle und transplantiertem Organ deutlich [16].…”
Section: Grundlagenunclassified
“…Patients with fulminant hepatic failure, RRT, and retransplantation are at particular risk for IA and may be considered for prophylaxis with an agent with activity against filamentous fungi (echinocandins, voriconazole, or amphotericin). (11,12) Abbreviations: HR-LTR, high-risk liver transplant recipient; IA, invasive aspergillosis; IFI, invasive fungal infection; RCT, randomized controlled trial; RRT, renal replacement therapy; TENPIN, Liver Transplant European Study Into the Prevention of Fungal Infection.…”
mentioning
confidence: 99%